Income Inequality under Colonial Rule: Evidence from French Algeria, Cameroon, Tunisia, and Vietnam and Comparisons with British Colonies 1920-1960 - Facundo Alvaredo; Denis Cogneau; Thomas Piketty (African Economic History Network (AEHN), 2020)
In this article we assess income inequality across French and British colonial empires between 1920 and 1960. For the first time, income tax tabulations are exploited to assess the case studies of French Algeria, Tunisia, Cameroon, and Vietnam, which we compare to British colonies and dominions. As measured by top income shares, inequality was high in colonies. It fell after WWII, but stabilized at much higher levels than in mainland France or the United Kingdom in the 1950s. European settlers or expatriates comprised the bulk of top income earners, and only a minority of autochthons could compete in terms of income, particularly in Africa. Top income shares were no higher in settlement colonies, not only because those territories were wealthier but also because the average European settler was less rich than the average European expatriate. Inequality between Europeans in colonies was similar to (or even below) that of the metropoles. In settlement colonies, the post-WWII fall in income inequality can be explained by a fall in inequality between Europeans, mirroring that of the metropoles, and does not imply that the European/autochthon income gap was reduced.
Keywords: N31; N35; N37; O15; O53; O55; 330; Inequality; Top incomes; Colonialism; Africa; Asia